Diabetic Foot Care: Awareness and Practices among Diabetic Patient and Role of Preventive Education for Foot Ulceration in Developing Country, “SAVE FEET SAVE LIVES” (Journal of Pakistan Orthopaedic Association, 2024)
Background: foot ulcers are among the most complication in Diabetic patients worldwide. At the same time, regular care and timely evaluation of the foot ulcer or abrasion may lead to the prevention and reduction in the number of Diabetic foot diseases. Rising prevalence of diabetes mellitus can be associated with higher incidence of diabetic foot diseases. For this reason, diabetic patients are required to routinely practice the self-care of foot.Method: A cross-sectional study was conducted in the public sector hospital of Karachi, Sindh, including 258 patients diagnosed with Diabetes Mellitus. Knowledge and Foot care practice in Diabetic patients were assessed by a questionnaire filling. Then after patients under the study were given one hour education session regarding diabetic foot care. In the one year follow up duration, the incidence of Diabetic foot disease was assessed in these patients.Results: The mean age of patients with DM was 36 years. With respect to grading of knowledge, 24.8% had good, 35.65% had satisfactory and 39.53% had poor knowledge of foot care. The grading of practice of foot care was revealed as 14.23% had good, 46.89% had satisfactory and 36.82% had poor practices of foot care.Conclusion: lack of good knowledge and practice of foot care in diabetic patients revealed in our study and this study demonstrated the potential role of educating the patients with incidence and outcomes of the diabetic foot ulcers.